Performance Evaluation of Stone Export - Abolghasem Ebrahimi (مطالعات مدیریت راهبردی, 2013)
This study was aimed to investigate the weakness factors of Lorestan stone export based on Porter's Diamond Model. The statistical population of the study experts and managers associated with export and managers of manufacturing firms and export stone in Lorestan. In this study, In this study, due to limited statistical population a census method for was used to collect data and 39 question questionnaires were designed by the researcher the alpha coefficient was 84% Information obtained from the questionnaires. The t test revealed that according to Porter's Diamond Model, six factors including the internal factors, domestic demand conditions, related and supporting industries, firm strategy, structure and rivalry, events unforeseen and government role are effective in weakness factors of Lorestan stone export. The Friedman test shows that factors associated with government role the greatest impact and factors associated with demand conditions the lowest impact are in weakness factors of Lorestan stone export.